STRATEGI PROMOSI PEWEKA CLOTHING DI CV. DWIPUTRA IHWA - Asep Hermawan; Imas Widowati; Alwi Mauludin; Wanwan Jamaludin (Jurnal Teknologika, 2022)
This study aims to analyze the most appropriate promotional strategies used by CV. Dwiputra to introduce Peweka clothing products as premium quality T-shirt products with image designs carrying the characteristics of Purwakarta so that it can promote also Purwakrta City . Based on the results of field surveys for promotions, Peweka Cloth has implemented a Promotional Mix consisting of Advertising (adverting), Sales Promostion, Personal Sales (Personal selling), Direct Sales (Direct Marketing). Based on the analysis of sales results, interviews with owners and staff of employees and consumers who are visiting the Peweka Cloth gallery can be concluded that marketing media with online media such as social media and marketplaces can increase product sales and can better recognize Peweka Cloth products so that they can be known by consumers both locally and nationally as one of Purwakarta's signature souvenirs. In addition, the promotion is not only using online media, but there are direct sales in collaboration with local companies such as Bank BTN, Dawood Cafe & Resto, and Expo Auto 2000 located in Purwakarta City. Which aims to introduce the product directly to prospective customers. And product sales based on company data that have been done by Peweka Cloth, tend to be more in Offline media than online media.